Silicon-on-Insulator Waveguide Devices for Broadband Mid-Infrared Photonics - Bowei Dong; Xin Guo; Chong Pei Ho; Bo Li; Hong Wang; Chengkuo Lee; Xianshu Luo; Guo-Qiang Lo (IEEE Photonics Journal, 2017)
In this paper, we demonstrate silicon-on-insulator (SOI) channel waveguides with propagation loss and $r$ = 10 $μ$ $\text{m}$ bends with bending loss as low as 2 dB/cm and 0.02 dB/90 $^{° }$ in the broad wavelength range of 3.68–3.88 $μ$ $\text{m}$ . We also indicate the limitation of SOI waveguide loss in mid-infrared wavelength by analyzing loss mechanisms. Based on this high-performance mid-infrared waveguide, we systematically analyze the coupling efficiency of various directional couplers, which are critical and commonly used building blocks for on-chip light routing and power splitting. By varying coupling length and sweeping wavelength, the performance of directional coupler with various gap separations is meticulously investigated in 3.68–3.88 $μ$ $\text{m}$ . A experimental database for directional coupler with any power splitting ratio is provided. Our results offer a promising broadband platform for dense wavelength division multiplexing (DWDM) and applications that require precise control of coupling such as racetrack resonator in the mid-infrared region.